Combatting plant diseases with ant chemicals: A review and meta‐analysis. Issue 1 (20th September 2021) - Offenberg, Joachim; Jensen, Ida Cecilie; Hansen, Rikke Reisner
Abstract: Plant diseases are a growing threat to plant production and food security. An accumulating number of studies show that ants and their bacterial symbionts produce antibiotics that are potentially effective against plant pathogens. From 14 publications covering 246 ant antibiotic‐pathogen combinations, we evaluated the effectiveness of ant‐derived chemicals (produced by ants or their microbiomes) in combatting plant pathogens. In a meta‐analysis, we quantified the effect of ant chemicals on plant pathogens and compared it with the effect on other micro‐organisms. Twenty‐two ant secretions and 30 ant symbionts inhibited 20 and 10 plant pathogens, respectively, including major plant diseases and resistant strains. Ant‐derived antibiotics showed broad‐spectrum effects. Ant chemicals were antagonistic to plant pathogens in 93% of all tested combinations and microbiomes in 19%. All tested ant species contained antagonistic ant chemicals, and 10 of the 12 examined ant microbiomes contained at least one antagonistic symbiont. Ant chemicals had an overall negative effect on micro‐organisms and were more detrimental to plant pathogens compared to other micro‐organisms. Policy implications . By showing that ant‐derived antibiotics inhibit a wide range of economically important plant pathogens, we emphasize the potential of ant chemicals and live ants to protect plants. We recommend attention to this topic and provide recommendations for future research and management directions that may facilitate a new path in the development of efficient and sustainable plant protection. Abstract : By showing that ant‐derived antibiotics inhibit a wide range of economically important plant pathogens, we emphasize the potential of ant chemicals and live ants to protect plants. We recommend attention to this topic and provide recommendations for future research and management directions that may facilitate a new path in the development of efficient and sustainable plant protection. Photo credits: Jens H. Petersen.